2016
DOI: 10.1080/19443994.2015.1059370
|View full text |Cite
|
Sign up to set email alerts
|

A two-year field study and evaluation of water quality and trophic state of a large shallow drinking water reservoir in Shanghai, China

Abstract: A B S T R A C TReservoirs have been widely constructed all over the world in recent years to alleviate the shortage of water resources. Nevertheless, the assessment method of water quality and its trophic status needs to be developed. In this study, water quality parameters of a newly constructed shallow reservoir were regularly monitored for a period of two years, which is used as a major drinking water source of Shanghai, China. Furthermore, the trophic state indices of the reservoir were investigated based … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 32 publications
0
12
1
Order By: Relevance
“…The current results (9 < TN/TP < 26) confirmed that there were no obvious nutrient limitation tendencies for phytoplankton growth in the reservoir ( Figure S3). However, a previous study suggested that the reservoir is P limited [26]. Compared to that study, TP in the current study was much higher.…”
Section: Effects Of Nutrient and Light Availability On Phytoplankton contrasting
confidence: 85%
See 3 more Smart Citations
“…The current results (9 < TN/TP < 26) confirmed that there were no obvious nutrient limitation tendencies for phytoplankton growth in the reservoir ( Figure S3). However, a previous study suggested that the reservoir is P limited [26]. Compared to that study, TP in the current study was much higher.…”
Section: Effects Of Nutrient and Light Availability On Phytoplankton contrasting
confidence: 85%
“…The ratio between the euphotic and mixing depths (Zeu/Zmix) was used as a measure of light availability [35]. Trophic state index (TSI) values were calculated based on the method described in the study of Liu et al [26]. For main nutrient seasonal variation in each section, sampling sites were taken for replicates as follows: S1 and S12 for estuary, S2 and S3 for upstream, S4 to S6 for midstream, S7 to S11 for downstream.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Increases in water demand, as well as in water pollution in some countries, have led to the construction of reservoirs to ensure water quality and availability, especially in highly urbanized regions (Lehner et al 2011;Liu et al 2016). In South America, economic development is resulting in increased requirements for water storage and energy production.…”
Section: Introductionmentioning
confidence: 99%